2018
DOI: 10.1097/brs.0000000000002292
|View full text |Cite
|
Sign up to set email alerts
|

Early Impact of Postoperative Bracing on Pain and Quality of Life After Posterior Instrumented Fusion for Lumbar Degenerative Conditions

Abstract: 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 21 publications
0
42
1
Order By: Relevance
“…The reason why there were no significant postoperative differences between the postoperatively applied LSO may be related to why LSO was applied postoperatively in the first place. Previous studies have compared non-surgical and postoperative patients with LSO or without LSO and showed variable and controversial results [1,3,5,27,28]. Soliman et al [1] analyzed 43 patients who underwent PSIF for lumbar degenerative conditions and reported that postoperative bracing did not show better improvement in the quality of life and pain relief.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reason why there were no significant postoperative differences between the postoperatively applied LSO may be related to why LSO was applied postoperatively in the first place. Previous studies have compared non-surgical and postoperative patients with LSO or without LSO and showed variable and controversial results [1,3,5,27,28]. Soliman et al [1] analyzed 43 patients who underwent PSIF for lumbar degenerative conditions and reported that postoperative bracing did not show better improvement in the quality of life and pain relief.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have compared non-surgical and postoperative patients with LSO or without LSO and showed variable and controversial results [1,3,5,27,28]. Soliman et al [1] analyzed 43 patients who underwent PSIF for lumbar degenerative conditions and reported that postoperative bracing did not show better improvement in the quality of life and pain relief. A meta-analysis has also shown that bracing after lumbar surgery for degenerative disease did not correlate with an improvement in outcome [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 71 Controversy exists regarding the routine use of orthoses in the post-operative period of spine surgery—despite their widespread use, there is a lack of evidence of its cost-effectiveness in most spinal pathologies. 70 - 74 …”
Section: Introductionmentioning
confidence: 99%
“… 76 Studies examining this practice have been plagued with errors in research methodology including small sample sizes and various sources of bias, and no strong evidence yet exists to demonstrate clear benefit. 74 …”
Section: Introductionmentioning
confidence: 99%